Formation of Interstellar Bubble: A Time Dependent Numerical Simulation - Aryal, B; Devkota, A; Weinberger, R (Scientific World, 2010)
We present results of the numerical simulations for the first 105 years of the development of spherically symmetric interstellar bubbles. We have assumed three phase interstellar medium (ISM) model and estimated the size of the interstellar bubbles (ISB). Our results are based on calculations including 106 virtual stellar wind particles. We discuss the result in the context of Asymptotic Giant Branch (AGB) star, Proto-Planetary Nebula (PPN) phase and Relativistic Wind (RW) star. The size of the ISB is found 0.14 pc to 9.03 pc in the case of AGB (Asymptotic Giant Branch) star. This size increases for the PPN and RW phase to 0.64 - 40.28 pc and 2.83 pc - 178.12 pc, respectively. It is found that the ISB can survive in the case of cold and warm interstellar medium. In the hot ISM, the ISB can not be formed due to the AGB wind. The bubble can survive in the case of PPN phase stellar wind for all kinds of the ISM. In addition, we found that the bubble can be formed in the case of RW when the ISM is hot. In the cold ISM, the ISB can not be formed due to the RW. In the warm ISM, bubble can be formed due to the relativistic (pulsar) wind if the mass loss rate is extremely high. In the warm ISM, the overall size of the bubble increases but do not exceed the recommended limit. Our result indicates that the hot ISM can not be considered as a good environment for the existence of the ISB. The size of the bubble exceeds the recommended limit (i.e., 1 to 5 kpc) in both the PPN and RW phase. However, suitable AGB wind can trigger the environment for a bubble in the hot ISM. The results of this work should be compared with the observations in the future. Key words: Interstellar medium; Stellar wind; Planetary nebula; Pulsar. DOI: 10.3126/sw.v6i6.2626 Scientific World, Vol. 6, No. 6, July 2008 8-15